2019
DOI: 10.1002/smll.201903892
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of Local Spin Transition Behaviors in Thin Molecular Films by Bimodal AFM

Abstract: Thin films of the molecular spin‐crossover complex [Fe(HB(1,2,4‐triazol‐1‐yl)3)2] undergo spin transition above room temperature, which can be exploited in sensors, actuators, and information processing devices. Variable temperature viscoelastic mapping of the films by atomic force microscopy reveals a pronounced decrease of the elastic modulus when going from the low spin (5.2 ± 0.4 GPa) to the high spin (3.6 ± 0.2 GPa) state, which is also accompanied by increasing energy dissipation. This technique allows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Besides, as the SCO phenomenon is also accompanied by a concomitant change of the mechanical, dielectric, and magnetic properties of the material, other approaches can be implemented to probe the thermal spin transition, instead of optical readout. Among them, quantitative AFM mechanical (Young's modulus) measurements 48,49 can be used to probe the temperature changes in the SCO-thin-film thermometer, providing higher spatial resolution, though at the detriment of the temporal resolution and ease-of-use.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, as the SCO phenomenon is also accompanied by a concomitant change of the mechanical, dielectric, and magnetic properties of the material, other approaches can be implemented to probe the thermal spin transition, instead of optical readout. Among them, quantitative AFM mechanical (Young's modulus) measurements 48,49 can be used to probe the temperature changes in the SCO-thin-film thermometer, providing higher spatial resolution, though at the detriment of the temporal resolution and ease-of-use.…”
Section: Resultsmentioning
confidence: 99%
“…242 Local spin transitions in thin molecular films have been determined by following the temperature dependence of the Young's modulus from the low to the high spin states. 243 In another application, it was reported that the surface elasticity of binary self-assembled monolayers increased with ligand ordering. 244 The local elastic and inelastic properties of polymer films, polymer-based materials 214,245 and flexible crystals 246 have been extensively studied by bimodal AFM.…”
Section: Bimodal Afmmentioning
confidence: 99%
“…The study of the dynamical properties of the spin-state switching process within the hysteretic region of SCO nano-objects [13,50] remains the ultimate experimental challenge. In this context, the use of scanning probe microscopy [51][52][53] and transmission electron microscopy [54,55] methods opens up interesting perspectives. By analogy to superparamagnetism, it is possible that, below a certain critical size, the nanoobject behaves as a single entity in which all SCO molecules switch coherently, without activation of the heterogeneous nucleation and growth process.…”
Section: Discussionmentioning
confidence: 99%